1996
DOI: 10.1029/95jd01374
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric sampling of Supertyphoon Mireille with NASA DC‐8 aircraft on September 27,1991, during PEM‐West A

Abstract: The DC-8 mission of September 27, 1991, was designed to sample air flowing into Typhoon Mireille in the boundary layer, air in the upper tropospheric eye region, and air emerging from the typhoon and ahead of the system, also in the upper troposphere. The objective was to find how a typhoon redistributes trace constituents in the West Pacific region and whether any such redistribution is important on the global scale. The boundary layer air (300 m), in a region to the SE of the eye, contained low mixing ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…During the PEM‐West B mission, air samples were collected from February to March 1994. One major feature in the vertical profiles of CH 3 Cl during PEM‐West A (Figures 7‐15–7‐17) is the enhanced concentrations observed at high altitude (above 10 km), which reflect transport of CH 3 Cl by typhoons [ Newell et al , 1996; Blake et al , 1997; Kondo et al , 1997]. The model results show little vertical variation and did not reproduce those elevated concentrations.…”
Section: Resultsmentioning
confidence: 96%
“…During the PEM‐West B mission, air samples were collected from February to March 1994. One major feature in the vertical profiles of CH 3 Cl during PEM‐West A (Figures 7‐15–7‐17) is the enhanced concentrations observed at high altitude (above 10 km), which reflect transport of CH 3 Cl by typhoons [ Newell et al , 1996; Blake et al , 1997; Kondo et al , 1997]. The model results show little vertical variation and did not reproduce those elevated concentrations.…”
Section: Resultsmentioning
confidence: 96%
“…We also find two convective transport cases during fall 2001 (out of four) where transport in typhoons resulted in export of Asian pollution to the upper troposphere (E1, Table 2). Indeed, Newell et al [1996] and Blake et al [1996] reported elevated concentrations of O 3 , CO and hydrocarbons in the upper tropospheric convective outflow of typhoons during PEM‐West A in the fall of 1991. Springtime convection over SE Asia exports biomass‐burning emissions to latitudes south of 35°N (section 4.2), thus seldom reaching the CPO region.…”
Section: Seasonal Variations In the Mechanisms Of Transpacific Transportmentioning
confidence: 99%
“…In 1991 the DC-8 sampled the Typhoon Mireille from the boundary layer to the upper troposphere up to 12 km (Newell et al, 1996); the boundary layer eye region showed increased levels of ozone but at higher levels there was no evidencefrom ozone lidar cross sections -of increased ozone from downward entrainment of stratospheric air into the eye upper region; this indeed showed low tropospheric values.…”
Section: Cyclones In the Utlsmentioning
confidence: 99%